EDUKASI KONSEP DASAR MANAJEMEN DALAM ORGANISASI PADA SISWA AKUNTANSI KELAS XII SMK PERMATA HARAPAN BATAM - Sahara Sahara; Miftahul Ilmi; Rudi Yanto Batara Silalahi (Fakultas Teknik, Universitas Bangka Belitung, 2022)
The role of management is very important in moving the organization, where through the management process is expected to achieve goals effectively and efficiently. Effective means indicating that the objectives can be achieved in accordance with the planning, while efficient means that the tasks at hand are carried out correctly, organized and on schedule. It shows students need role of management that the result of this dedication activities are students unserstand the basic concepts of management in an organization to students majoring in accounting at SMK Permata Harapan, especially class XII. Therefore, our dedication brings goals to carry out activities to educate on the basics management organizations for their softskill knowledge of basic management concepts which is useful as a provision in finding a job. The method of this dedication activities use the method starting from the review, preparation, implementation of activities, evaluation and publication. The results of this dedication activities are students understand the basic concepts of management, improve their knowledge and resources in management and achieve organizational goals.